Fabrication of curved overhanging thin-walled structure with robotic wire and arc additive manufacturing (RWAAM). Issue 1 (19th August 2019) - Li, Yifeng; Qin, Xunpeng; Wu, Qiang; Hu, Zeqi; Shao, Tan
Abstract : Purpose: Robotic wire and arc additive manufacturing (RWAAM) is becoming more and more popular for its capability of fabricating metallic parts with complicated structure. To unlock the potential of 6-DOF industrial robots and improve the power of additive manufacturing, this paper aims to present a method to fabricate curved overhanging thin-walled parts free from turn table and support structures. Design/methodology/approach: Five groups of straight inclined thin-walled parts with different angles were fabricated with the torch aligned with the inclination angle using RWAAM, and the angle precision was verified by recording the growth of each layer in both horizontal and vertical directions; furthermore, the experimental phenomena was explained with the force model of the molten pool and the forming characteristics was investigated. Based on the results above, an algorithm for fabricating curved overhanging thin-walled part was presented and validated. Findings: The force model and forming characteristics during the RWAAM process were investigated. Based on the result, the influence of the torch orientation on the weld pool flow was used to control the pool flow, then a practical algorithm for fabricating curved overhanging thin-walled part was proposed and validated. Originality/value: Regarding the fabrication of curved overhanging thin-walled parts, given the influences of the torch angles on the deposited morphology, porosity formation rate and weld pool flow, the flexibility of 6-DOF industrial robot was fully used to realize instant adjustment of the torch angle. In this paper, the deposition point and torch orientation of each layer of a robotic fabrication path was determined by the contour equation of the curve surface. By adjusting the torch angle, the pool flow was controlled and better forming quality was acquired.